Research on Teaching College Economics: A Survey - Siegfried, John J.; Fels, Rendigs (Journal of Economic Literature, 1979)
We are indebted to Elisabeth Allison, G. L. Bach, William Becker, Frank Bonello, Kenneth Boulding, Stephen Buckles, J R. Clark, George Dawson, Daniel Fusfeld, Malcolm Getz, W Lee Hansen, RobertHeilbroner, RobertHighsmith, CliffHuang, ThomasJohnson, Allen Kelley, Darrell Lewis, Michael MacDowell, Campbell McConnell, Richard McKenzie, David Morawetz, Donald Paden, Phillip Saunders, Alex Scott, Howard Tuckman, John Vahaly, Henry Villard, Burton Weisbrod, Arthur Welsh, and Thomas Zak for comments on an earlier draft; to Thomas Overstreet and James Lewek for research assistance; to the members of Economics 380, Kaye James, Noel Lim, Katherine Maddox, Hal McClure, Mary Ann Meiners, and George Nomikos, for papers and discussions on economics education; to Violet Sikes for typing; and to Marjorie Churchill for editorial assistance.